1992
DOI: 10.1159/000186862
|View full text |Cite
|
Sign up to set email alerts
|

Role of Agglomeration in Calcium Oxalate Monohydrate Urolith Development

Abstract: Formation of agglomerates of calcium oxalate monohydrate (COM) crystals on semi-batch precipitation peformed at conditions relevant to urolithiasis (37°C, pH = 6, initial ratio [Ca]/[Ox] = 10), but without any specific admixture, was followed by both optical and electron microscopy. COM crystals formed on precipitation developed into large agglomerates consisting of intergrown crystals by a mechanism of primary agglomeration. Primary agglomeration of COM crystals represents an important mechanism of COM renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…On these phosphates, COD crystals can easily nucleate, as demonstrated in a previous paper [11], or the phosphates can be covered by organic material. On COD crystals or organic material, COM crystals can easily nucleate, initiating genesis of the stone core by primary agglomeration [12], The deposit of or ganic material on this core stops its growth and enables the beginning of the growth of the compact columnar COM zone [10]. This process is shown in figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…On these phosphates, COD crystals can easily nucleate, as demonstrated in a previous paper [11], or the phosphates can be covered by organic material. On COD crystals or organic material, COM crystals can easily nucleate, initiating genesis of the stone core by primary agglomeration [12], The deposit of or ganic material on this core stops its growth and enables the beginning of the growth of the compact columnar COM zone [10]. This process is shown in figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of some aggregates on the pellet surface, despite the absence of significant crystalluria, demonstrates that such aggregates were formed through primary aggregation. Primary aggrega tion consists of a type of crystal malgrowth that takes place on the surface of already developed crystals, the socalled parent crystals [12], This process results in concre tions consisting of intergrown crystals with a complex crystal arrangement as observed in the core of COM cal culi [13], From these facts it can be concluded that sapo nins can produce important inhibitory effects in the heter ogeneous nucleation on hydrophobic materials, but no important action must be expected on heterogeneous nucleation on calcium phosphates or in primary aggrega tion.…”
Section: Discussionmentioning
confidence: 99%
“…macromoléculas, restos celulares y lesiones epiteliares, los fármacos y sus metabolitos son nucleantes heterogéneos a considerar (Grases 1992 -Hipercalciuria. El aumento de la excreción urinaria de calcio (hipercalciuria) es un factor común que contribuye a la urolitiasis de CaOx en los seres humanos, gatos y perros (Welk y Buffington, 2003;de Groat et al, 1993;Sands et al, 2000).…”
Section: Epidemiologíaunclassified